Strategy Development Model Management as an Implication of Agent of Change in Pesantren-Based Schools - Syndhi Pramitika Sari; Linayati Lestari; Zulkifli Zulkifli (Jurnal Inovasi Pendidikan dan Sains, 2025)
The management of strategy development models in the context of pesantren-based schools plays a significant role in creating meaningful changes across various aspects of education. This study aims to identify and analyze a strategy development model that can be implemented at SMP Az-Zainiyah Nahdatul Wathan as part of efforts to foster change and innovation in education, particularly in addressing the rapidly growing challenges of globalization while considering local wisdom and religious values embedded in pesantren education. This study used a qualitative research methodology with a management approach, which focused on the curriculum integration development model implemented at SMP Az-Zainiyah Nahdatul Wathan. The effective strategy development model involved several stages, starting from the analysis of the internal and external situations of the pesantren, identification of strengths and weaknesses, opportunities, and threats faced, to the formulation of appropriate strategies to achieve educational objectives. This process included the development of a relevant curriculum, the improvement of human resource quality, and the utilization of technology to support the teaching and learning process. Through this study, it was found that the successful development of an effective management-based strategy could strengthen the role of pesantren as an educational institution by producing graduates with high academic achievement as well as strong moral integrity. By implementing this model, SMP Az-Zainiyah Nahdatul Wathan is prepared to face challenges and changes in the global education landscape